Extractability and crop transfer of potentially toxic elements from mediterranean agricultural soils following long-term sewage sludge applications as a fertilizer replacement to barley and maize crops. (May 2018) - Iglesias, Mònica; Marguí, Eva; Camps, Francesc; Hidalgo, Manuela
Graphical abstract: Highlights: Repeated biosolid application increase extractability of Cu, Se, Sb, Cd, As and Zn. PTE content in cereal grains do not increase after the use of sludge except for As. Extractable As content in soils and total As in barley grains shows correlation. Abstract: Sewage sludge is used as a fertilizer replacement in agricultural soils for its chemical properties, such as organic matter content, and for its capability to improve physical soil characteristics like porosity. This is also an appealing disposal option for residue whose production is increasing worldwide. However, there is some concern about the presence of potentially toxic elements (PTEs) that can accumulate in soils and become available for crops. In this work, a study was conducted to evaluate the extractability and crops transfer of thirteen PTEs from soils that had been amended with biosolids each year for 15 years as a regular agricultural practice. The study was conducted with barley (winter cereal) and maize (spring cereal) crops. After this long period, an increase in the amount of Pb, Hg, Zn and Ag in soils amended by biosolids was confirmed. However, it is important to emphasize that the PTE total content in croplands was still far below the thresholds established by US and European regulations. Statistically significant differences were also found between the soils fertilized with biosolids and other treatments compared with the potential phytoavailable amount of Cu, Se, Sb and especially for As and Zn, by a DTPA leaching test. Despite these results, the concentration of PTEs in the barley and maize grains grown in fields repeatedly amended with biosolids was not statistically different from those grown with chemical fertilization, except for As in barley grains. In this case, a significant correlation was found between the DTPA-extractable As content in soils and the total content in grains (r = 0.83).